Prediction of Pressure Drop Correction to Suit Wax Deposition Modeling in Annular Test Section - Ibrahim, M.A. (PETRONAS, 2009)
An experimental loop set up used in this study is dedicated to model the wax deposition in oil and gas transportation. The flow behavior and the pressure drop throughout the test section were investigated in order to justify the usage of the system. The test section has an annular shape of 3 m length, 0.0422 m ID and .0801 m OD. Oil is re-circulated in the annular passage while a cold water-glycol mixture is re-circulated in the inner pipe and counter currently to the oil flow. The experiments were carried out at annulus Reynolds number range of 400 to 17000 with different flow conditions. It was noted that the calculated pressure drop values were considerably higher than the measured ones and the differences increase with the flow rate increments. The equivalent length method has been used as a correction technique to characterize the pressure drop in the test section. After applying the correction method, the analysis revealed that the test facility can yield a pressure drop prediction with an accuracy of 5%.